2003
DOI: 10.1590/s1678-77572003000400013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tooth age on bond strength to dentin

Abstract: his in vitro study evaluated the effect of tooth age on the tensile bond strength of Prime & Bond NT adhesive system to dentin. Human third molars from the five age groups were analyzed: A-17 to 20yrs, B-21 to 30yrs, C-31 to 40yrs, D-41 to 50yrs and E-51 to 63yrs. The occlusal enamel was removed using a diamond saw under water cooling and the dentin surface was wet-ground with 600-grit SiC paper to obtain flat surfaces. The adhesive system was applied according to the manufacturer's instructions and a 6-mm hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Our results were in accordance with the literature which revealed that age did not influence the bond strength of any adhesives tested (Giannini et al ,. Brackett et al ,.…”
Section: Discussionsupporting
confidence: 93%
“…Our results were in accordance with the literature which revealed that age did not influence the bond strength of any adhesives tested (Giannini et al ,. Brackett et al ,.…”
Section: Discussionsupporting
confidence: 93%
“…Age did not affect bond strength values of glass-ionomer based, all-in-one, single-step, self-etching adhesive system to dental hard tissues. [444546]…”
Section: Variables Influencing Micro-bond Strength Test Resultsmentioning
confidence: 99%
“…In addition, it was shown that age factor may affect bond strength 33,34,35. For this reason, superficial dentin layers from the teeth which were collected from the patients with the age group between 20 and 30 were used in present study for both standardization and higher bond strength.…”
Section: Discussionmentioning
confidence: 99%